2010
DOI: 10.1097/dbp.0b013e3181e416ae
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Paper Diary Recording of Infant and Caregiver Behaviors

Abstract: For behavioral recording of infant and caregiver behaviors, mothers generally expressed more approval for e-diaries than paper diaries, but neither was considered onerous. E-diaries consistently report more frequent but similar durations of behaviors. If recording when convenient, daily diary entries trend toward 2 to 3 entries a day. The e-diary results provide convergent evidence that paper diary recordings of common infant and caregiver behavior durations provide good estimates of durations, but that behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…Either an e-diary or a paper diary is useful in objectively measuring both duration of crying and behavior of caregivers. 11 This will improve the comparability of studies regarding insights in cause and treatment of these infants.…”
Section: Definition Of Excessive Cryingmentioning
confidence: 98%
“…Either an e-diary or a paper diary is useful in objectively measuring both duration of crying and behavior of caregivers. 11 This will improve the comparability of studies regarding insights in cause and treatment of these infants.…”
Section: Definition Of Excessive Cryingmentioning
confidence: 98%
“…New parents have many demands on their time, and Fig. 3 Histograms demonstrating distortion in age of emergence from researcher assessments compared to continuous unified electronic (CUE) diary method data, with lines of best fit electronic diaries have previously been shown to offer greater ease of use than paper and pencil diaries (Lam et al, 2010). As a result, electronic diaries as a method encourage compliance and continued participation (Stone et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies that have involved parental reporting of infant behavior have focused on crying and sleeping, states that are both easily identified (Lam et al, 2010). To ensure that maternal reporters could remember and identify specific behaviors correctly, we developed a training and support system to accompany the electronic diaries.…”
Section: Training Maternal Reportersmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, several studies of children and adults with asthma have shown decreased compliance and reliability of data in those completing a mobile diary compared to a paper diary. 26,27 Additionally a study of parental report of infant sleep habits suggested poorer compliance in patients completing an electronic version compared to a paper version.…”
Section: Discussionmentioning
confidence: 99%